PENERAPAN MODEL PEMBELAJARAN BERDASARKAN MASALAH UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII1 SMP BHAYANGKARI PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to fixed the learning process and improve the mathematical problem solving ability through implementation of Problem Based Learning (PBL) model. This type of research is the classroom action research with two cycles. Research conducted in the junior high school class VIII1 Bhayangkari Pekanbaru in the first semester of the school year 2016/2017, with the subject of 20 learners. The research instrument consists of learning tools and instruments to collect data. Learning device used in this study is the syllabus, lesson plans and activity sheet. Data collection instruments used in the study was the observation sheet and mathematical problem solving test. Data analysis technique used is qualitative data analysis descriptive narrative and descriptive statistical analysis of quantitative data. Based on this research, the learning process has improved and mathematical problem solving ability of the learners increased after applying the Problem Based Learning (PBL) Problem Based Learning model can be used as an alternative to learning, because through this learning can improve the learning process and improve mathematical problem solving ability of the learners.Keywords: Problem Based Learning, Mathematical Problem Solving Ability, learning process.